Bipolar clavicle fractures treatment using medial and lateral double plates: A case report. Issue 3 (21st January 2022) - Xing, Haiyang; Cao, Changpeng; Chen, Xinxiao; Gao, Yang; Huang, Guanning; Zhu, Jiajing; Wang, Gang
Abstract: Rationale: Clavicle fractures are common, accounting for 2.6 to 4% of all fractures, which typically result from direct injuries, including direct force on the shoulder after falling. However, bipolar clavicle fractures are rare, accounting for only 2.8% of all clavicle fractures, and their injury mechanism is speculated to evolve from two independent and continuous forces affecting the clavicle. Due to its low incidence, there is great controversy regarding the treatment of this fracture, as there is no relevant treatment standard or guideline to date. Patient concerns: In this case report, we describe a rare case of bipolar clavicle fracture in a 76-year-old man with multiple systemic fracture complications due to a traffic injury. He presented with limited shoulder function and movement upon arrival in the emergency room. Diagnosis: Bipolar clavicle fracture in the right shoulder (Robinson type 1B2, Robinson type 3B2) Interventions: We performed trans-sternoclavicular locking plate and lateral clavicular hook plate treatments and instructed patients to perform reasonable postoperative functional exercises. Outcomes: Three months postoperatively, the pain was almost completely relieved with a DASH score of 40.0. Furthermore, radiographic examination of the clavicle showed satisfactory fracture healing. The patient had no further demands for shoulder function and no irritative symptoms of internal fixation and refused to undergo a second operation. The patient had a satisfactory prognosis after the treatment. Lessons: The treatment of bipolar clavicle fractures remains controversial. This study provides evidence of a feasible method to treat bipolar clavicle fractures: trans-sternoclavicular locking plate and lateral clavicular hook plate treatment.